Manajemen Mutu Pendidikan Pondok Pesantren As-Salafiyyah Asy-Syafi’iyyah Tambakberas Barat Jombang - Shobiri, Mochammad Syafiuddin; Wafa, M Aliyul; Hidayat, Rohmat (JoEMS (Journal of Education and Management Studies), 2023)
The study focuses on the Quality Management of Education of the As-Salafiyyah Asy-Syafi’iyyah Residence, located in Tambakberas West Jombang. Research It aims to investigate and provide insight into school management practices to improve the quality of education. Using a qualitative descriptive approach, this research falls into the field research category. Research was conducted on administrators, ustadz/dzah, and staff members associated with the agency. As-Salafiyyah Asy-Syafi’iyyah in Jombang has implicitly adopted the principle of Total Quality Management (TQM), in particular emphasizing the concept of Juran Trilogy. This approach is used as a means of continuing to maintain and improve the quality of education in the Cottage. To improve this quality, it is essential to formulate a strategic plan based on the findings of SWOT analysis. This analysis identifies the key success factors that stem from the assessment of strengths, weaknesses, opportunities, and threats. The proposed strategies include SO (Strengths-Opportunities), ST (Deficiency-Threats), WO (Weaknesses-Possibility) and WT strategies. (Kecurangan-Amaran). This strategy collectively aims to develop a comprehensive plan for the As-Salafiyyah Asy-Syafi’iyyah Hostel, ultimately advancing the goal of quality education in the Peesantren Hostel.